A remotely controlled NIR-II photothermal-sensitive transgene system for hepatocellular carcinoma synergistic therapy. Issue 25 (14th June 2021) - Qiao, Shuangying; Xin, Fuli; Wu, Ming; Zheng, Youshi; Zhao, Bixing; Zhang, Cuilin; Liu, Xiaolong; Wei, Zuwu; Liu, Jingfeng
Abstract : The here reported SPNHT nano-system with the ability of NIR-II PTT and photothermal-triggered TRAIL in situ expression possessed an admirable synergistic anti-cancer efficacy for HCC. Abstract : Photothermal therapy (PTT) exhibits an excellent therapeutic effect in cancer treatment, but some cancers are still facing rapid recurrence due to the presence of heat-resistant cells, which express heat shock proteins (HSP) to defend against hyperthermia. Inspired by optogenetics, we firstly designed a caged TNF-related apoptosis-inducing ligand (TRAIL) expressing plasmid under HSP70 protomer (HSP70-TRAIL) as the thermal-activated gene therapy agent to induce the apoptosis of heat resistant cells. Then, the caged HSP70-TRAIL was decorated on the surface of the photothermal agent (semiconducting nanoparticles, SPNs) through electrostatic adsorption to obtain SPN@HSP70-TRAIL-GFP (SPNHT). Under 1064 nm near-infrared second region (NIR-II) laser irradiation, the SPNHT acted as an emerging photothermal agent for PTT. Importantly, the caged HSP70-TRAIL could be further activated by PTT to express TRAIL on demand to concurrently kill survival cells for overcoming the problem of tumor recurrence after PTT. Both in vitro and in vivo studies demonstrated that the SPNHT nano-system with the ability of NIR-II photothermal-triggered TRAIL in situ expression possessed an admirable synergistic anti-cancer efficacy for HCC. This work offers new tactics for effective treatment of cancer, which showed a great significance for reducing the rate of cancer recurrence after PTT treatment.